Drinking water cost and its impact on living standard in pallikuda gramaniladhari division (kn/65) of kilinochchi district, sri lanka - Sujiththa, S. (University of Jaffna, 2018)
The main objective of this study is to identify the drinking water cost that how to affect on the people living standard. Especially cost of drinking water dominates a major part of expenses for households in Pallikuda GN division. Thus, in the year of 2016 data has been employed for this cross sectional analysis. Stratified and random sampling technique was used to get exactly unbiased data for scrutinized in this study. The regression model were fitted and estimated in this study. As with the correlation analysis, there is average positive correlation level which is 0.520 between total cost for gathering drinking water and income. The P value 0.000 also conform that this is nicely fitted. And also R2 is 0.27 which means that approximately 27% of variance in expenditure of gathering drinking water is explained by income. Furthermore, there is high positive correlation which is 0.820 between total expenditure for gathering drinking water and family members and correlation is highly significant at the 0.01 level. The regression also appears highly strong and it has R2 value that 0.673 explains to 67 percentage of factors which influences between family member and total expenditure for gathering drinking water. As further analysis there is low positive correlation between total expenditure for gathering drinking water and distance between home and drinking water source. The study highly insists the need for adapting new and effective projects for solving drinking water problem which enhance people’s living standard.
Keywords: Drinking water; Expenditure; Income; Living standard